Financial Empowerment and Health Related Quality of Life in Family Scholar House Participants - Chelsey Franz (Journal of Financial Therapy, 2016)
Research demonstrates an association between poverty and health. Populations in poverty suffer from poor mental and physical health, and thus, poor health-related quality of life. Research also indicates people living in the lower socio-economic categories experience higher levels of stress that are associated with these health declines. Family Scholar House, a local community intervention designed to alleviate poverty and improve socio-economic status by providing college education and support to single parents, combats these health outcomes by addressing the five social determinants of health (economic stability, education, social and community context, health care, and neighborhood and built environment). Quantitative analysis indicates an improvement in mental health among Family Scholar House participants: 0-12 month participants reported significantly more mentally unhealthy days than a control group; however, this difference is no longer significant at the end of participant’s time in the program. Qualitative analysis suggests this improvement may be due to stress reduction related to increased economic stability and financial security gained through an intentional implementation of a financial empowerment curriculum within the Family Scholar House program. Implementation of financial empowerment into community programs designed to alleviate poverty may improve mental health and thus health-related quality of life.
Keywords: Quality of life; financial empowerment; mental health; poverty; community support